Adaptive management: Promises and pitfalls - McLain, Rebecca J.; Lee, Robert G. (Environmental Management, 1996)
Proponents of the scientific adaptive management approach argue that i t increases knowledge acquisition rates, enhances information flow amo ng policy actors, and provides opportunities for creating shared under standings. However, evidence from efforts to implement the approach in New Brunswick, British Columbia, Canada, and the Columbia River Basin indicates that these promises have not been met. The data show that s cientific adaptive management relies excessively on the use of linear systems models, discounts nonscientific forms of knowledge, and pays i nadequate attention to policy processes that promote the development o f shared understandings among diverse stakeholders. To be effective, n ew adaptive management efforts will need to incorporate knowledge from multiple sources, make use of multiple systems models, and support ne w forms of cooperation among stakeholders.